Political financing in the Commonwealth - Pinto-Duschinsky, Michael (Commonwealth Secretariat LondonGB, 2001)
Provides a summary of laws and practices in Commonwealth countries concerning the financing of election campaigns and political parties. Points to some specific problems and issues relevant to these countries.